y ′ = ln ( x y ′ − y )
Given the differential equation above, y ( 1 ) = − 1 , y is twice differentiable, and y ′ ′ ( x ) = 0 .
Evaluate y ( e ) .
Notation:
e
≈
2
.
7
1
8
2
denotes the
Euler's number
.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Note that y ( x ) = − 1 (the constant function) is also a solution. You "lost" this solution when you divided both sides of the equation by y ′ ′ .
Log in to reply
Thank you, Jon! I've updated the problem statement accordingly.
Log in to reply
I don't get how the problem was updated: y = − 1 is still a solution!
This equation actually boils down to a Clairaut's Equation . Right?
You have assumed that y is twice differentiable and that was not actually given.
We want to get rid of the ln ( x ) -function first, so we build two equations by applying the exp ( x ) -function and by differentiation:
e y ′ = x y ′ − y
y ′ ′ = x y ′ − y 1
By putting those two equations together we get: y ′ ′ = e y ′ 1 = e − y ′ .
Now substitute y ′ = v and get: v ′ = e − v . This can easily be solved: d x d v = e − v ⇔ ∫ e v d v = ∫ d x ⇒ e v = e y ′ = x
Substitute this result into our equation above: y ′ ′ = e y ′ 1 = x 1
Now solve this by integrating twice:
y ′ ′ = x 1 ⇒ y ′ = ln ( x ) + c 1 ⇒ y = x ( ln ( x ) − 1 ) + c 2
Now apply the initial condition y ( 1 ) = − 1 and get: y ( 1 ) = − 1 = 1 ( 0 − 1 ) + c 2 = − 1 + c 2 ⇒ c 2 = 0
At last we can solve the problem: y ( e ) = e ( 1 − 1 ) = 0
Problem Loading...
Note Loading...
Set Loading...
Let's us differentiate both sides of our DE with respect to x such that:
d x d [ y ′ = l n ( x y ′ − y ) ] ⇒ y ′ ′ = x y ′ − y ( y ′ + x y ′ ′ ) − y ′ = x y ′ − y x y ′ ′ .
This in turn results in x y ′ − y x = 1 ⇒ y ′ − x 1 y = 1 , which after introducing the integrating factor u ( x ) = x 1 now produces:
x 1 y ′ − x 2 1 y = x 1 ⇒ ( x y ) ′ = x 1 ⇒ x y = l n ( x ) + C
which after implementing the given boundary condition yields 1 − 1 = l n ( 1 ) + C ⇒ C = − 1 , or y ( x ) = x l n ( x ) − x .
We wish to compute y ( e ) , which equals y ( e ) = e [ l n ( e ) − 1 ] = e ( 1 − 1 ) = 0 .